2007
DOI: 10.1016/j.gaitpost.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gait speed on local dynamic stability of walking

Abstract: The focus of this study was to examine the role of walking velocity in stability during normal gait. Local dynamic stability was quantified through the use of maximum finite-time Lyapunov exponents, λ Max . These quantify the rate of attenuation of kinematic variability of joint angle data recorded as subjects walked on a motorized treadmill at 20%, 40%, 60%, and 80% of the Froude velocity. A monotonic trend between λ Max and walking velocity was observed with smaller λ Max at slower walking velocities. Smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
408
11
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(465 citation statements)
references
References 25 publications
(38 reference statements)
29
408
11
4
Order By: Relevance
“…This approach, however, is not without controversy. For example, England & Granata [100] and Kang & Dingwell [101] found increased LEs at increasing walking speeds indicating decreased dynamic stability at higher speeds. On the other hand, Bruijn et al [87] using LEs at different walking speeds (in young cohorts) found both increasing and decreasing stability values at a higher speed depending on the estimates used (l_s versus l_l) as well as the projected directions anteroposterior (AP) versus mediolateral (ML).…”
Section: Sources Of Heterogeneity Among Studiesmentioning
confidence: 99%
“…This approach, however, is not without controversy. For example, England & Granata [100] and Kang & Dingwell [101] found increased LEs at increasing walking speeds indicating decreased dynamic stability at higher speeds. On the other hand, Bruijn et al [87] using LEs at different walking speeds (in young cohorts) found both increasing and decreasing stability values at a higher speed depending on the estimates used (l_s versus l_l) as well as the projected directions anteroposterior (AP) versus mediolateral (ML).…”
Section: Sources Of Heterogeneity Among Studiesmentioning
confidence: 99%
“…Before beginning, it is important to note that because of space constraints, this review considers only a subset of the reports on this topic. For complementary perspectives, the reader is referred to other pertinent reviews (Chau, 2001a(Chau, , 2001bChau, Young, & Redekop, 2005;Hausdorff, 2005) as well as parallel studies by others (Buzzi, Stergiou, Kurz, Hageman, & Heidel, 2003;Costa, Peng, Goldberger, & Hausdorff, 2003;Dingwell, Cusumano, Cavanagh, & Sternad, 2001;Dingwell, Gu Kang, & Marin, 2006;England & Granata, 2007;Georgoulis, Moraiti, Ristanis, & Stergiou, 2006;Granata & England, 2006;Kurz et al, 2003;Kurz & Stergiou, 2005;Stergiou, Harbourne, & Cavanaugh, 2006). …”
mentioning
confidence: 99%
“…In addition, the number of embedding dimensions used in this study, i.e. nine, was higher than in many other studies [8,12,16,20] but is still within the range of five to twelve used in the literature [8,10,[12][13][14]16,18,20,24,30]. This broad range of embedding dimensions might be due to the use of different types of data, such as electromyography, joint angles, angular velocity or linear accelerations, and the embedding of one single signal or more; and might call for standardization of state space reconstruction in gait research.…”
Section: Kinematic Trunk Variabilitymentioning
confidence: 64%
“…The data series length was normalized to on average 99 samples per stride to eliminate the effect of varying data series length on the local dynamic stability estimates [16,20]. Subsequently, a state space was reconstructed using all three accelerations and their time-delayed copies [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation